Peran Gatekeeping Dalam Program Talkshow Rakyat Bersuara Live Di Inews (Studi Kasus) - Muhamad Junaedia; ‪christopher yudha erlangga (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
With communication, humans can connect and interact with other humans. Communication can also help in terms of information sharing and education, one of which is by using mass media. Information that is not clear about its truth and authenticity can cause social conflicts in society, therefore it is important to learn about the disadvantages and benefits obtained from the mass media. One of the mass media that is currently still trusted in terms of conveying information, be it an event, phenomenon, or entertainment, is the television media. Television is a means of communication media that plays a role in conveying messages to the audience, one of which is messages in the form of information or news related to public problems. The Voice People's Program aired on iNews is a program with a talk show format that discusses problems or events that are currently occurring. What is discussed in this study is about the Role of Gatekeeping in the Live Voice People's Talk Show Program on iNews, by using a descriptive qualitative research method with a constructivist paradigm through case study analysis, then the theory used is the Westley and Maclean's model Gatekeeping theory. The results of the study show the importance of the role of gatekeepers in the People's Voice program by going through several important stages, then there are several individuals who play an important role as gatekeepers. So that information conveyed to the public can be well received and worthy of being broadcast to the public through television media.